Synthesis of biosafe spirulina-derived carbon dots and their fluorescence imaging in zebrafish - Yue Wang; Zhizhi Gu; Jingyi Dong; Cunguang Liu; Jie Zhu; Zixu Wang; Jiaying Li; Meichen Lu; Jian Han; Shengnan Cao; Zhuang Xue; Yan Chen; et al. (Results in Chemistry)
Carbon dots (CDs) have emerged as promising fluorescent nanomaterials owing to their superior optical properties and favorable biocompatibility. In the present study, environmentally friendly CDs were synthesized from spirulina via a hydrothermal approach, and their bioimaging performance in zebrafish models was systematically evaluated. Through comprehensive fluorescence imaging and biological assessments, the biodistribution and biological effects of these biomass-derived CDs in embryonic and adult zebrafish were investigated, along with their potential impacts on developmental and physiological homeostasis. Spirulina-derived CDs exhibit prominent fluorescence properties, enabling high-quality imaging in zebrafish embryos and tissues. These CDs possess excellent tissue penetration capabilities and specific accumulation patterns, facilitating clear visualization of anatomical structures. In embryos, CDs preferentially accumulate in the yolk sac while preserving normal developmental progression. In adult zebrafish, distinct fluorescent signals are observed in the eye, nerve, and intestinal tissues. Transcriptome analysis revealed that CDs modulated metabolic pathways and extracellular matrix organization without inducing significant toxicity. Notably, exposure to CDs enhanced intestinal flora diversity by promoting beneficial bacterial phyla and reducing the abundance of Proteobacteria. Histological examinations confirmed that CDs administration improved intestinal integrity and reduced inflammatory markers, indicating potential immunomodulatory effects. This study highlights the excellent bioimaging capabilities and biocompatibility of spirulina-derived CDs in vertebrate models. Currently, imaging materials are associated with relatively complex toxicity profiles and staining procedures, making the development of low-toxicity and rapid-staining biological imaging agents an urgent necessity. The present findings provide valuable insights into the safe application of biomass-derived nanomaterials in biomedical imaging, while demonstrating their potential therapeutic benefits through microbiota modulation and anti-inflammatory effects, thereby supporting their future advancement in diagnostic and therapeutic applications.